Nonlinear variational inequalities on reflexive Banach spaces and topological vector spaces - Zeqing Liu; Jeong Sheok Ume; Shin Min Kang (International Journal of Mathematics and Mathematical Sciences)
The purpose of this paper is to introduce and study a class of nonlinear variational inequalities in reflexive Banach spaces and topological vector spaces. Based on the KKM technique, the solvability of this kind of nonlinear variational inequalities is presented. The obtained results extend, improve, and unify the results due to Browder, Carbone, Siddiqi, Ansari, Kazmi, Verma, and others.